OTIMIZAÇÃO DO PROCESSO DE PRODUÇÃO DE TIQUIRA EMPREGANDO ENZIMAS COMERCIAIS E FUNGOS ISOLADOS A PARTIR DOS BEIJUS UTILIZADOS NO MÉTODO TRADICIONAL - Bastos, Francisco Albuquerque (2013)
Tiquira, a strong content beverage from Maranhão ( Brazil ), obtained from cassava (Manihot esculenta Crantz.) has its production concentrated in several counties of the State, through a handmade process , rather primitive, in which the conversion of starch cassava is taken into fermentable sugars by fungi which is found on the native beijus of manioc where strains are picked at random. Alcoholic fermentation is also made by yeasts found in the environment. Its commercialization is practiced informally, making it difficult to record statistical data of production and the number of producers in the Ministry of Agriculture. In order to optimize this process, commercial enzymes, strains of fungi (Aspergillus niger), were used to in order to convert starch into fermentable wort and pressed yeasts for fermentation. The processes proposed here follow three steps: gelation of starch scarification and subsequent dextrinization the sugars, alcoholic fermentation and distillation of fermented wine. Substituting the mold for commercial enzymes in the proposed circumstances, the manufacturing of tiquira was performed in just 25 hours, whereas when using fungi isolated, the production of tiquira took approximately 136 hours for its processing. As one can see, there was a considerable reduction of time in the two cases presented here in relation to the traditional process, which takes approximately 20 days to achieve the distillate. It was also found that the fermentation and destillation of the wort resulting from the scarification of cassava is equivalent to that of cane sugar, and both processes can be processed with the same equipment by tiquira producers. It was shown that the concentrations of copper and ethyl carbamate were visibly reduced in comparison to the traditional process, enabling a better quality of the beverage, as well as reducing the risks to consumer health. From the experiments it can be concluded that the replacement of the traditional process by commercial enzymes, fungi isolated and pressed yeast are highly and technically recommended primarily to small producers.